NUTRITION STATUS CORRELATED TO THE FIRST PERMANENT MANDIBULAR MOLAR TEETH OF ELEMENTARY SCHOOL CHILDREN IN LINTAU BUO, TANAH DATAR REGENCY, WEST-SUMATRA - A., Syukra (INDONESIAN JOURNAL OF BIOMEDICAL SCIENCES, 2013)
The first permanent mandibular molar teeth is the most important for child, especially to stimulate growth of jaw. The teeth has normally erupted at children age of 6-7 years old. However, it is frequently not happened at this stage. This study aims to determine the nutritional status relate to the first permanent mandibular molars teeth eruption in the elementary school children age of 6-7 years old at Lintau Buo, Tanah Datar Regency, West-Sumatra Indonesia. This is an analytical cross-sectional study, with anthropometric measurements of body mass index/BMI of elementary school children related to eruption of the first permanent mandibular teeth. The results showed that nutritional status of elementary school children age of  6-7 years old for the most were within normal category (51.2%). Grade-I (6-7 years old) suffered from emaciation is still quite high (45.4%), 20.3% of 187 students who suffer from emaciation first permanent mandibular molars have erupted, the first permanent mandibular molars in first grade children (6-7 years old) with normal nutritional status, risk of overweight and obese have erupted. Nutritional status affects children’s first permanent mandibular molar erupted lower jow. The better the nutritional status of a child then the erupstion of the  first mandibular molars  will get better and grow in time.   Key words: nutritional status, tooth eruption, the first permanent mandibular molars, dental and oral health
Keywords: dent